2016
DOI: 10.1007/s11947-016-1716-z
|View full text |Cite
|
Sign up to set email alerts
|

Potential Production of Healthier Protein Isolate from Broiler Meat using Modified Acid-Aided pH Shift Process

Abstract: Protein isolates from broiler meat were produced using acid-aided process (AP) with some modifications including prewashing prior to pH shift process (PW), homogenisation with 5 mM citric acid plus 8 mM CaCl 2 (CA) and homogenisation with 5 % ethanol (EA). Significant reduction of total cholesterol, nucleic acids and haemoproteins with improved protein yield and whiteness of the isolate was obtained from all modified process (p < 0.05). CA was the most effective method in elimination of cholesterol (p < 0.05).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…In addition, the removal rate of haemoglobin treated by combining prewash by phytic acid and alkaline‐aided shift process was higher than that of haemoglobin treated by combining prewash by phytic acid and acid‐aided shift process. Panpipat & Chaijan (2016b) also employed combination of prewash treatment and acid‐aided shift process to obtain broiler meat proteins, and found that modified acid‐aided shift process could more effectively remove impurities in broiler meat, such as cholesterol, total nucleic acids and haemoglobins. The combination process could produce proteins with the higher yields and greater whiteness values.…”
Section: Combination Methods For Recovering Protein Isolatesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the removal rate of haemoglobin treated by combining prewash by phytic acid and alkaline‐aided shift process was higher than that of haemoglobin treated by combining prewash by phytic acid and acid‐aided shift process. Panpipat & Chaijan (2016b) also employed combination of prewash treatment and acid‐aided shift process to obtain broiler meat proteins, and found that modified acid‐aided shift process could more effectively remove impurities in broiler meat, such as cholesterol, total nucleic acids and haemoglobins. The combination process could produce proteins with the higher yields and greater whiteness values.…”
Section: Combination Methods For Recovering Protein Isolatesmentioning
confidence: 99%
“…pH‐shift process has been also utilised to recover protein isolates from various sources, for example fish, fish‐processing by‐products, meat and egg processing products (Azadian et al ., 2012; Kristinsson et al ., 2013; Panpipat & Chaijan, 2016b, 2020; Chaijan & Panpipat, 2018; Lynch et al ., 2018; Surasani, 2018). Currently, this process is particularly popular in recovering functional protein isolates from aquatic products and their processing wastes (Surasani et al ., 2018a,b; Hinchcleiffe et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…hydrophobic interaction, disulfide bond and hydrogen bond. However, the extreme denaturation showed a negative impact on gelation of muscle proteins (Panpipat and Chaijan 2016).…”
Section: Expressible Dripmentioning
confidence: 98%
“…The sol was then stuffed into polyvinylidine casing with a diameter of 2.5 cm and both ends of the casing were sealed tightly. The sol was then incubated at 40°C for 30 min, followed by heating at 90°C for 20 min (Panpipat and Chaijan 2016). The gels were cooled in iced water and stored for 24 h at 4°C prior to analysis.…”
Section: Gel Preparationmentioning
confidence: 99%
“…Mireles DeWitt, Nabors, and Kleinholz (2007) imply the structure of acid‐treated catfish protein is more easily opened compared to untreated samples while adjusting the pH to neutral. Many studies have demonstrated that acid treatment improves the gel quality of meat proteins (Cortés‐Ruiz et al., 2016; Panpipat & Chaijan, 2016). Wang, Wu, and Betti (2013) suggest that there are more disulfide bonds formed for acid‐aided proteins, which might be induced by higher pro‐oxidant activity of acid‐treated hemoglobin.…”
Section: Isoelectric Solubilization/precipitationmentioning
confidence: 99%